Estimating the Direct Medical Outpatient Costs of Diagnosis and Treatment of Trichomoniasis Among Commercially Insured Patients in the United States, 2016 to 2018. Issue 3 (18th March 2021) - Kumar, Sagar; Chesson, Harrell; Gift, Thomas L.
Abstract : We used 2016–2018 medical claims data to estimate the cost of diagnosing and treating trichomoniasis. We estimated the total direct medical cost to be 213 per case of trichomoniasis. Abstract: We used 2016–2018 outpatient claims data to calculate direct outpatient medical costs per case of trichomoniasis in 2019 US dollars. The outpatient, drug, and total costs per treated case of trichomoniasis were 174, 39, and 213, respectively. Total costs were higher for female patients (220) than for male patients (158).